Managing fractures in geriatrics: Current approaches and update - Tito Sumarwoto; Dhimas Hartanto; Pamudji Utomo (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Geriatric fractures refer to fractures that occur in older people, typically resulting from low-energy trauma and accompanied by osteoporosis. The bone remodelling process imbalance significantly contributes to age-related bone loss in geriatric, which reduces bone mass, making them more susceptible to fractures. Managing geriatric fractures poses unique challenges due to the presence of other comorbid conditions that can interfere with the healing process. Thus, restoring stability is prioritised over reversing anatomy and biology. The use of medication is often helpful in treating osteoporosis. Diagnosing and managing geriatric fractures is a complex process that requires careful consideration of various comorbid factors associated with older patients. Both non-operative and operative management requires thorough preparation. The primary goal of fracture management in older people is to achieve patient independence. Factors such as age, gender, comorbid conditions, pre-fracture functional abilities, and fracture type can impact the outcome regarding ambulation, daily activities, and quality of life. Therefore, it is essential to consider all these factors while managing geriatric fractures.